2020
DOI: 10.3390/tropicalmed5040153
|View full text |Cite
|
Sign up to set email alerts
|

Geno-Spatial Distribution of Mycobacterium Tuberculosis and Drug Resistance Profiles in Myanmar–Thai Border Area

Abstract: Worldwide, studies investigating the relationship between the lineage of Mycobacterium tuberculosis (MTB) across geographic areas has empowered the “End TB” program and understand transmission across national boundaries. Genomic diversity of MTB varies with geographical locations and ethnicity. Genomic diversity can also affect the emergence of drug resistance. In Myanmar, we still have limited genetic information about geographical, ethnicity, and drug resistance linkage to MTB genetic information. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…1 ). The first three have been reported in many Asian studies 5 , 8 , 13 . L1.1.3.4, was identified mostly among African samples (Supplementary Table S3 ), particularly in Malawi (69%).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…1 ). The first three have been reported in many Asian studies 5 , 8 , 13 . L1.1.3.4, was identified mostly among African samples (Supplementary Table S3 ), particularly in Malawi (69%).…”
Section: Resultsmentioning
confidence: 85%
“…Associations between each of these sublineages with geography have been studied. For example, L1.1.1.1 is predominant in Vietnam 7 , L1.1.3 is common in Myanmar 8 , Bangladesh 9 and East Africa 10 while L1.1.2.2 and L1.2.2 (previous L1.2.1) are associated with India and Southeast Asia, respectively 5 . Interestingly, around 80% of Mtb isolates in the Philippines, a high TB burden country, belonged to the last sublineage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The geographic distribution of lineages revealed that strain diversity varied among the hospitals of the region. This difference could reflect patient-location differences ( Maung et al, 2020 ). As whole-genome sequencing is very expensive, we could not sequence all of the Mtb isolates identified from participants attending the respective study sites (hospitals) in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also align with recent studies combining spatial and WGS data to study TB transmission in several other high burden settings, including China (33,34), Ghana (41), and along the Thai-Myanmar border (36). Observed spatial patterns among related Mtb strains have included local and regional distributions of genotypic cluster groups (39,41) and lineages (42), and associations between residential proximity and genetic similarity (33,34) In contrast, a study in China found the majority of genotypic groups included participants from separate geographic districts (43). However, that study differed from ours because it specifically analyzed MDR-TB, and included a majority of participants (70%) that had migrated from other provinces (43).…”
Section: Discussionmentioning
confidence: 99%